(untitled) (Journal of the College of Basic Education, 2022)
Representative is the main source live on stage to the sound, so that the vocabulary, dialogue and diction represents the main factor for the transfer of meaning to the recipient, so the actor dialogue property depends as semantic holder, in order to achieve this level has to be the representative to reach the training and development of vocal abilities to get to the technique the most appropriate and useful to achieve this requirement, and to achieve it has become imperative for the actor to employ all Tnoath rhythmic and tonal sound and transitions, and among these techniques is toning element as the aesthetic value gives the representative sense and honesty in performance, so research two topics I contains, the concept of toning, Bosfih process melodic controls the wholesale level bands, through speed control and falling rhythm verbal, and the second topic was titled, Jobs toning, as an aesthetic value higher his functions govern the conduct of tonalities process and confirmed by their contexts of words, whether Astvhammep or his two or confirmation, then search procedures - community Search and appointed intentionality and analysis they carry the concept of toning attributes, then the results and discussion, conclusions, recommendations, suggestions, and finally the list of sources.